Further Treatment Intensification in Undifferentiated and Rheumatoid Arthritis Patients Already in Low Disease Activity has Limited Benefit towards Physical Functioning - Sytske Anne Bergstra; Otto Olivas; Gülşah Akdemir; Naghmeh Riyazi; Gerard Collée; Johannes H. L. M. van Groenendael; Robert B. M. Landewé; Cornelia F. Allaart (Arthritis Research & Therapy, 2017)
Abstract Background It is recommended to optimise treatment as long as a predefined treatment target is not met, but should the aim be remission if patients are in low disease activity (LDA)? The aim of this study was to assess if, in patients with rheumatoid arthritis (RA) or patients with undifferentiated arthritis (UA) with Disease Activity Score (DAS) ≤ 2.4 (LDA), treatment intensification results in better functional ability. Methods In the IMPROVED study 610 patients with early RA or UA were treated with methotrexate + tapered high-dose prednisone. After 4 months, patients with DAS ≥ 1.6 were randomised to either of two treatment strategies. Patients with DAS < 1.6 tapered treatment. Over 5 years, patients with DAS ≥ 1.6 required treatment intensification, but protocol violations occurred, which allowed us to test the effect of treatment intensification regardless of subsequent DAS. A linear mixed model was used to test, in patients in LDA, the relationship between treatment intensification and functional ability (Health Assessment Questionnaire [HAQ]) over time. Results The number of patients in LDA per visit ranged from 88 to 146. Per visit, 27–74% of the patients in LDA had treatment intensification. We found a statistically significant effect of treatment intensification on ΔHAQ, corrected for baseline HAQ, age, sex and treatment strategy (β = −0.085, 95% CI −0.13 to −0.044). When ΔDAS was added, the effect of treatment intensification was partly explained by ΔDAS, and the association with HAQ was no longer statistically significant (β = −0.022, 95% CI −0.060 to 0.016). When the interaction between treatment intensification and time in follow-up was added, a statistically significant interaction was found (β = 0.0098, 95% CI 0.0010 to 0.019), indicating lesser improvement in HAQ after treatment intensification if follow-up time increased. Conclusions For patients with early RA and patients with UA already in LDA, further treatment intensification aimed at DAS remission does not result in meaningful functional improvement. Trial registration ISRCTN, 11916566 . Registered on 28 December 2006. EudraCT, 2006-006186-16 . Registered on 16 July 2007.